Optimization of the Secure and Safety Unit in Preventing Motor Vehicle Traffic Violations at Jepara Police (Advances in Police Science Research Journal, 2024)
The traffic situation in Jepara Regency is congested with a high number of residents and users of motorized vehicles. This situation is also supported by the increasing number of traffic violations committed by the community. This writing aims to describe the operational management of the Secure and Safety Unit of Jepara Traffic Police in preventing motorized vehicle traffic violations and to describe the collaboration of the Secure and Safety Unit of Jepara Traffic Police in preventing motorized vehicle traffic violations. The research was also conducted using a qualitative approach and data collection techniques through observation, interviews, and document review. In chapter II of conceptual literature, the author uses SWOT theory as a knife to analyzing influencing factors, as well as management theory and cooperation theory to discuss issues, optimization concepts, KamselUnit concepts, prevention concepts, violation concepts, traffic concepts, traffic violation concepts, concepts motorized vehicles to analyze the formulation of the problem in chapter I. The results of this research are the efforts of the Secure and Safety Unit of Jepara Traffic Police in preventing motorized vehicle traffic violations have been carried out, but there are still some deficiencies, starting from planning due to the absence of school targets, organizing due to lack of personnel and infrastructure, actuating due to the provision of material that not optimal and controlling because the Leadership Directive Event and consolidation were not carried out yet or after the activities are carried out. Based on the author's observations, the Secure and Safety Unit of Jepara Traffic Police must carry out community education activities about traffic as a whole to the community by paying attention to cooperation with parties that support the performance of the Secure and Safety Unit of Jepara Traffic Police so it can be carried out optimally so that the number of student traffic violations can decrease in Jepara Regency.
Keywords: Kata Kunci : Pencegahan, Pelanggaran Lalu Lintas, Unit Kamsel Satuan Lalu Lintas Polres Jepara